The Evolution of ESG Standards And Implications For Sustainable Development: A Critical Assessment From Sri Lanka’s Legal Framework - Shamila, D. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
Despite the increasing prominence of environmental, social, and governance (ESG) frameworks aimed at reducing the environmental and human rights impact of businesses, their adoption and implementation face challenges due to existing regulatory gaps that impede progress towards sustainable development. Companies need to embrace greater social and environmental responsibility for their daily operation. For instance, “Transforming our World” recognises the diversity within the private sector, which includes micro-enterprises, cooperatives, and multinationals, and calls upon all businesses to leverage their creativity and innovation to address sustainable development challenges. Accordingly, corporations bear significant responsibility for promoting the Sustainable Development Goals (SDGs), owing to their substantial capital and technological resources, which are vital for economic growth. However, they ranked as major polluters raising concerns about their impact on the ESG issues. Consequently, corporate governance (CG) principles emerge to address, to some extent, non-commercial matters such as ESG reporting. This ensures that corporations do not cause harm to society and the environment while pursuing their business objectives. Therefore, ESG criteria and the SDGs are interconnected components that reinforce the sustainability of corporations. This research employs a doctrinal methodology by utilising existing primary and secondary sources to explore the intersection between legal obligations and voluntary ESG practices. It incorporates both normative and descriptive aspects of stakeholder theory to evaluate corporate responsibilities within the legal framework and ESG landscape. The research concludes that CG is an evolving concept. In Sri Lanka, the legal framework for CG is not comprehensive enough to cover all the aspects of governance, given that CG encompasses a wide range of activities, from philanthropic initiatives focusing on community development to strategic intervention targeting pressing issues like climate change.
Keywords: ESG reporting; Corporate governance; CSR; SDGs; Sustainability